Analysis of the behavior of the flow of prices in the financial market using the entropy of information - Ponte Bejarano, José Luis (2023)
In the present work it is indicated that the entropy of the information is the most appropriate tool to analyze the behavior of the flow of prices in the financial market. For this, the following points are mentioned: general concepts of chaos theory applied to the financial market, concept of dynamic systems applied to the flow of prices, time series of prices and the entropy of information applied to the flow of prices in the financial market.